2012
DOI: 10.3182/20120829-3-mx-2028.00015
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Wind Turbine FDI Competition

Abstract: In this paper some newly published methods for fault detection and isolation developed for a wind turbine benchmark model are tested, compared and evaluated. These methods have been presented as a part of an international competition. The tested methods cover different types of fault detection and isolation methods, which include support vector machines, observer based methods, and auto generated methods. All of these methods show interesting potentials for usage in the wind turbine application, but all with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
(29 reference statements)
0
31
0
Order By: Relevance
“…It can be seen that the LPV ESO method can provide very good fault estimation, which is a significant result even though it is claimed that a 100 Nm fault is too small to be detected [13]. From the simulation results, there is no obvious improvement obtained by using the AFTC scheme.…”
Section: Actuator Fault In Generator Subsystemmentioning
confidence: 79%
“…It can be seen that the LPV ESO method can provide very good fault estimation, which is a significant result even though it is claimed that a 100 Nm fault is too small to be detected [13]. From the simulation results, there is no obvious improvement obtained by using the AFTC scheme.…”
Section: Actuator Fault In Generator Subsystemmentioning
confidence: 79%
“…At wind turbine level, this fault could be detected monitoring changes in the frequency spectra of the vibration measurements. However, the solutions provided in the Wind Turbine FDI competition suggest that it is hard to detect changes in the drive train damping only at the wind turbine level [40]. Hence, it is interesting to investigate if this fault could be detected at the wind farm level.…”
Section: B Fault Scenariosmentioning
confidence: 99%
“…The problem of model-based fault diagnosis in wind turbines has recently been addressed (Odgaard & Stoustrup, 2012b), the main motivation being the importance gained in many countries by this technology for electricity generation. So far, revising the literature, methods ranging from Kalman filters (Wei et al, 2008), observers (Odgaard et al, 2009), parity equations (Dobrila & Stefansen, 2007), dynamic weighting ensembles (Razavi-Far & Kinnaert, 2013) and fuzzy modeling and identification methods (Badihi et al, 2013) have already been suggested as possible model-based techniques for fault diagnosis of wind turbines.…”
Section: Introductionmentioning
confidence: 99%